Environmental conservation based on Mamar system as local wisdom of West Timor, East Nusa Tenggara - Lewoleba, G.; Widianarko , B.; Dewi , Y. T. N. (Man and Environment. Issues of Neoecology, 2023)
Purpose. To analyze the environmental conservation practices based on the Mamar system as local wisdom and related social structures as a mechanism for environmental conservation in West Timor, East Nusa Tenggara. Results: Mamar system has persisted since the 17th century since it is applied with mechanisms and approaches to the needs of local communities for the preservation of natural resources in the long and sustainable term. This system is applied by cultivating land for perennials, food crops, fodder crops, and livestock rearing.. Environmental conservation is implemented on the basis of the local principles such as Bua, Nuni, and Bunu. The local customary regulations were set and supervised by the guards called Mataf and Ketiut Po’an, in which the individuals who violated the regulations will get a sanction called Tasane. By adhering to the local belief system, the community naturally consider that their action in taking a use of natural resources wisely is part of maintaining the sustainability. Besides, the local community also pursue the harmonious relationship with the inhabitants of a particular forest area or spring through ritual ceremonies. Conclusions: Practically, Mamar can be interpreted as an “artificial oasis: built by Amarasi local community in West Timor as a strategy to adapt in the adverse environmental conditions. Mamar system sustained the socio-economic and cultural life of the Amarasi community through its’ ecological, economic and social variables. The conservation based on Mamar system is carried out and maintained by applying the local values that are authentic, straightforward and measurable in accordance with the situation and conditions of the community